Supercritical CO2 fracturing with different drilling depths in shale. Issue 4 (21st December 2022) - Yang, Hongwei; Zhao, Yuan; Zhang, Xinghua; Liu, Guojun; Du, Xidong; Delei, Shang; Yu, Yongjun; Chen, Juan; Wang, Hui; Tu, Huaijian
ABSTRACT: Shale gas is a crucial unconventional natural gas; carbon dioxide is a serious greenhouse gas. Therefore, using supercritical carbon dioxide as a fracturing fluid can fracture shale reservoirs and exploit shale gas as well as store carbon dioxide to slow the greenhouse effect. In this study, supercritical carbon dioxide fracturing experiments were conducted at different drilling depths. They showed that structural failure pressure decreased with the increase in borehole and sealing lengths owing to the larger excavation damage zone induced by borehole drilling. During the fracturing process, acoustic emission signals were recorded, which exhibited similar development tendencies, and this process could be divided into four parts based on the acoustic emission characteristic. The saltation of fluid pressure was due to the saltation of isothermal compression and expansion occurring in phase change processes. Moreover, crack morphology before and after the fracturing were scanned and rebuilt by computed tomography instruments, which displayed that an effective fracturing crack could be generated by supercritical carbon dioxide. Although the cark morphology was relatively simple, a complex crack could be formed at a deep drilling depth as revealed by the comparisons of the box dimension, crack perimeter, and crack area at different drilling depths. Based on the acoustic emission accumulation counts, a damage variable was introduced to describe failure degree. Furthermore, based on a previous work and the damage characteristic and fluid pressure features, the entire process of supercritical carbon dioxide fracturing could be divided into five main stages. In addition, the chemical reaction between the shale matrix and the fracturing fluid was analyzed. The supercritical fracturing fluid could dissolve and remove substances, improving the shale porosity and connectivity.